Interaction of tau with HNRNPA2B1 and N6-methyladenosine RNA mediates the progression of tauopathy - Jiang, Lulu; Lin, Weiwei; Zhang, Cheng; Ash, Peter E.A.; Verma, Mamta; Kwan, Julian; van Vliet, Emily; Yang, Zhuo; Cruz, Anna Lourdes; Boudeau, Samantha; Maziuk, Brandon F.; Lei, Shuwen; et al. (Molecular cell, 2021)
The microtubule-associated protein tau oligomerizes, but the actions of oligomeric tau (oTau) are unknown. We have used Cry2-based optogenetics to induce tau oligomers (oTau-c). Optical induction of oTau-c elicits tau phosphorylation, aggregation, and a translational stress response that includes stress granules and reduced protein synthesis. Proteomic analysis identifies HNRNPA2B1 as a principle target of oTau-c. The association of HNRNPA2B1 with endogenous oTau was verified in neurons, animal models, and human Alzheimer brain tissues. Mechanistic studies demonstrate that HNRNPA2B1 functions as a linker, connecting oTau with N6-methyladenosine (m6A) modified RNA transcripts. Knockdown of HNRNPA2B1 prevents oTau or oTau-c from associating with m6A or from reducing protein synthesis and reduces oTau-induced neurodegeneration. Levels of m6A and the m6A-oTau-HNRNPA2B1 complex are increased up to 5-fold in the brains of Alzheimer subjects and P301S tau mice. These results reveal a complex containing oTau, HNRNPA2B1, and m6A that contributes to the integrated stress response of oTau. [Display omitted] •Tau oligomerization exhibits rapid aggregation of proteins linked to RNA metabolism•Oligomeric tau complexes with HNRNPA2B1 and m6A-RNA to regulate RNA translation•Knockdown of HNRNPA2B1 reduces the response to pathological tau•m6A progressively increases with disease severity in human AD brains Oligomerization of microtubule-associated protein tau recruits RNA binding proteins and methylated RNA transcripts, termed N6-methyladenosine RNA. This complex regulates the stress response and inhibits protein synthesis. In Alzheimer’s disease and related models, this complex becomes persistent and pathological, leading to tau fibrillization, nuclear membrane disruption, and progressive neurodegeneration.